Investigation of different graphene oxides coated on tapered optical fiber sensor for aqueous ethanol detection - Md Rosli, Mohd Anwarul Arif (2016)
Sensing devices, especially optical sensors, are becoming increasingly popular in the last decade. Typically, evanescent-field optical fiber sensors utilize tapered or etched fiber structure to enhance the evanescent filed interaction with the sensing medium. This makes the fiber fragile and difficult to handle. This research focuses on designing and analysing a multimode fiber to be used as a sensor for the detection of aqueous ethanol. A nanostructured sensing layer is applied to further enhance the sensitivity of the sensor. This study investigates the use of tapered fiber tip sensor coated with different types of Graphene oxide (GO) which is GO (unsonicated), GO (sonicated) and GO 1-Ethyl-3-[3-dimethylaminopropyl] carbodiimide hydrochloride (EDC+NHS). The effect of nanostructured layers each types of (GO) are investigated towards the performance improvement of the optical sensor. GO nanostructures have huge surface area that enhances the sensor-analyte interaction and thus, improves the sensing performance. GO nanostructured materials also react chemically with ethanol molecules, resulting in an increase in the sensitivity of the sensor. Optimization of the each types of GO layer and the tapering parameters are done and the sensing capability of the device is tested using different concentrations of ethanol in water which are 20%, 40, 60%, 80% and 100% of ethanol concentration. The sensor demonstrates high sensitivity to aqueous ethanol when interrogated in the visible region using a spectrometer and light source. The GO coated tapered fiber sensor with 50 μm is compared with other works and its demonstrated high sensitivity in intensity and absorbance with a response and recovery time of approximately 25 and 35 seconds respectively.